Synergistic activation of ERK1/2 between A-fiber neurons and glial cells in the DRG contributes to pain hypersensitivity after tissue injury. Issue 1 (March 2018) - Yamakita, Shunsuke; Horii, Yasuhiko; Takemura, Hitomi; Matsuoka, Yutaka; Yamashita, Ayahiro; Yamaguchi, Yosuke; Matsuda, Megumi; Sawa, Teiji; Amaya, Fumimasa
Background: Intense nociceptive signaling arising from ongoing injury activates primary afferent nociceptive systems to generate peripheral sensitization. ERK1/2 phosphorylation in dorsal root ganglion can be used to visualize intracellular signal activity immediately after noxious stimulation. The aim of this study was to investigate spatiotemporal characteristics of ERK1/2 phosphorylation against tissue injury in the primary afferent neurons. Methods: Plantar incisions were made in the hind paws of Sprague-Dawley rats (n =150). Levobupivacaine was injected into the plantar aspect of the paws and ankles, Mitogen-activated protein kinase kinase (MEK) inhibitor was injected into the paw, and carbenoxolone, dual inhibitor of the gap junction and pannexin channel, was intraperitoneally injected. Pain hypersensitivity was investigated by a behavioral study, while phosphorylated ERK1/2 was detected in dorsal root ganglion and hind paw using immunohistochemistry and Western blot. Results: Phosphorylated ERK1/2 was induced in dorsal root ganglion (26.8 ± 2.9% at baseline, 65.6 ± 3.6% at 2 min, and 26.3 ± 3.4% at 2 h) after the incision. NF-200 positive A-fiber neurons and satellite glial cells were positive for phosphorylated ERK1/2. Injury-induced pain hypersensitivity was abolished by MEK inhibitor. Levobupivacaine treatment inhibited phosphorylated ERK1/2 induction, carbenoxolone treatment inhibited glial phosphorylated ERK1/2 at 2 min after the injury, and carbenoxolone inhibited pain hypersensitivity and neuronal phosphorylated ERK1/2 at 1 h after the injury. Conclusion: ERK1/2 phosphorylation in A-fiber neurons and satellite glial cells immediately after injury contributes to the generation of pain hypersensitivity. Signal communication between neurons and satellite glial cells expands the duration of neuronal ERK1/2 phosphorylation and pain hypersensitivity at 1 h after tissue injury.